Purchasing behaviour of UiTM students Sabah branch on T-shirt / Suziana Sandhu - Sandhu, Suziana (2008)
This research is study on 'Purchasing Behavior of UiTM Sabah Students on Tshirt'. As we know that T-shirts are manufactured by the textile industry. They are typically made of cotton or polyester fibers (or a mix of the two), knitted together in a jersey stitch that gives a T-shirt its distinctive soft texture. T-shirts are often decorated with text and/or pictures. T-shirt fashions include styles for men and women, and for all age groups, including baby, youth and adult sizes. Thus, the main objective of this research is to understand the purchasing behavior among UiTM Sabah Students towards t-shirt and to determine their preference too. Apart the significant of this study will give good impact firstly to the entrepreneurs, then to the respondents and lastly to the researcher as well. Two types of data collection method are used. They are primary data and secondary data. Where primary data in this research, questionnaires will be design in order to guide researcher to interview respondents and secondary data are information, which are already in existences, but are relevant to this study. Two types of secondary were used. There are internal and external secondary data. Internal sources are those data is gathered within the organization that the research had carried out. These include information that collected from magazines, newspaper, pamphlets and others. External sources are those data that is collected outside the organization. These include data that is gathered from Internet, projects paper and other published document from libraries. Based on the analysis of the survey, it was found that the findings and results of the survey are concurrent with literature and there some problem encountered and some suggestions to solve. Overall of this research, from the finding and analysis, researcher made the conclusion that most of the UiTM Sabah students prefer any design as their design style on their t-shirt and prefer other brand such as Padini, Cheetah, Esprit, Deosel and many more as the most popular t-shirt brand. The students like to spend RM20 to RM30 to buy one t-shirt. The most of students bought t-shirt as their necessity.